Litigation and settlement under court error - Philipp Ackermann (University of Bern, Department of Economics, 2010)
Settlements are often considered to be welfare-enhancing because they save time and litigation costs. In the presence of court error, however, this conclusion may be wrong. Court decisions create positive externalities for future litigants which will not occur if a dispute is settled out of court. Focusing on private litigation, we examine the impact of court error on the deterrent effect of the strict liability rule. In an asymmetric information setup both, underdeterrence and overdeterrence are possible under court error. Moreover, court error increases the likelihood of out-of-court settlements which can offset the positive externality of litigation.
Keywords: K13; K41; 330; litigation; settlement; asymmetric information; court error; strict liability rule; Rechtsprechung; Zivilprozess; Verhandlungen; Asymmetrische Information; Rechtsökonomik